Soil applied silicon and manganese combined with foliar application of 5-aminolevulinic acid mediate photosynthetic recovery in Cd-stressed Salvia miltiorrhiza by regulating Cd-transporter genes - Sun, Yuee; Li, Xin; Najeeb, Ullah; Hou, Zhuoni; Buttar, Noman Ali; Yang, Zongqi; Ali, Basharat; Xu, Ling (Frontiers in Plant Science, 2022)
Salvia miltiorrhiza is an important medicinal plant that experiences significant growth and biomass losses when cultivated on cadmium (Cd) contaminated soils. High Cd accumulation in plant tissues also increases the risk of metal entry into the food chain. In this study, we proposed that Cd accumulation in S. miltiorrhiza can be restricted through plant growth regulators and nutrient management. Therefore, S. miltiorrhiza seedlings were transplanted into mixed nutrient soil for two weeks, then treated with 30 mg kg-1 CdCl2, 200 mg kg-1 Na2SiO3·9H2O, and 100 mg kg-1 MnSO4, and simultaneously sprayed with 10 mg L-1 ALA on the leaves one week later. This study showed that elevated Cd accumulation significantly reduced plant growth and biomass. This growth inhibition damaged photosynthetic machinery and impaired carbon assimilation. In contrast, 5-aminolevulinic acid (ALA) significantly promoted the biomass of S. miltiorrhiza, and the dry weight of plants treated with ALA combined with manganese (Mn)/silicon (Si) increased by 42% and 55% as compared with Cd+Mn and Cd+Si treatments. Exogenously applied ALA and Si/Mn significantly activated antioxidant enzymes and promoted the growth recovery of S. miltiorrhiza. Further, exogenous ALA also reduced the Cd concentration in S. miltiorrhiza, especially when combined with Si. Compared with the Cd+Si treatment, the Cd+Si+ALA treatment reduced the Cd concentration in roots and leaves by 59% and 60%, respectively. Gene expression analysis suggested that ALA and Si significantly up-regulated genes associated with Cd transport. Other genes related to heavy metal tolerance mechanisms are also regulated to cope with heavy metal stress. These results indicated that the combined action of ALA and Si/Mn could reduce Cd-toxicity by increasing chlorophyll content and changing oxidative stress and can also affect Cd accumulation by regulating gene expression.